Impact of systemic inflammatory response activation on the risk of coronary conduit dysfunction and the incidence of cardiovascular events after coronary artery bypass grafting - Yu. I. Buziashvili; I. V. Koksheneva; D. Kh. Kamardinov; E. F. Tugeeva; I. P. Shuvaev; A. Sh. Iraskhanov; E. P. Golubev; R. M. Ibragimov; V. Yu. Buziashvili; O. M. Sherstyannikova (Российский кардиологический журнал)
Aim. To assess the influence of systemic inflammatory response activation on the incidence of coronary conduit dysfunction and the risk of cardiovascular events after coronary artery bypass grafting, as well as to identify the most significant humoral markers.Material and methods. The study included 84 patients with stable coronary artery disease who underwent examination and isolated coronary artery bypass grafting (CABG). Humoral inflammation markers were assessed before surgery, 24 hours and 7 days after CABG. Control coronary bypass angiography was performed intraoperatively and 1 year after CABG. An analysis of clinical and paraclinical data was performed in two following groups: Group 1 — patients (n=10) diagnosed with bypass graft dysfunction (D+) during control bypass angiography 1 year after surgery; Group 2 — patients (n=74) without bypass graft dysfunction (D-) according to control bypass angiography 1 year after CABG.Results. Coronary conduit dysfunction was detected in 10 (12%) patients 1 year after CABG, which was caused by venous bypass graft thrombotic occlusion in 7 (70%) cases, and hemodynamically significant bypass graft stenosis in 3 (30%) cases. The following adverse cardiovascular events were registered in these patients: cardiovascular death — 2 patients; recurrent angina — 8 (80%) patients; acute myocardial infarction — 4 (40%) patients; hospitalization due to decompensated heart failure — 2 (20%) patients; repeated myocardial revascularization — 8 (80%) patients; life-threatening arrhythmias (ventricular tachycardia) — 3 (30%) patients. These patients had significantly higher levels of hs-C-reactive protein (hs-CRP), fractalkine, IL-1β, neopterin at all testing time points (before surgery, 24 hours and 7 days after CABG), indicating a more pronounced activation of inflammatory mechanisms.Conclusion. The study confirmed the leading role of inflammation in triggering and maintaining the main mechanisms determining coronary conduit damage after CABG, which is the basis for bypass graft dysfunction. This allows us to consider inflammation as an independent cause of vascular damage, and the established significant inflammatory biomarkers (hs-CRP, fractalkine, IL-1β, neopterin) as predictors of bypass graft dysfunction and infavorable outcomes of myocardial revascularization.